?DISTRIBUTION OF HEAVY METALS IN THE SEDIMENTS OF LAGOS LAGOON (Biological Sciences - PJSIR, 2000)
The concentrations of cadmium, lead, nickel, chromium, copper, zinc, iron, manganese, cobalt and mercury in the sedi- ments of the Lagos lagoon were determined by atomic absorption spectrophotometry in the year 1995. The respective ranges of the concentrations ofthe metals were Cd:0.13-S.60, Pb:4.10-295. 70,Ni: 11.60-149.40, Cr:23.30-167.20, Cu:4.S0- 102.70, Zn:27.30-323.70, foe:10579.80-85548.00, Mn:276.00-748.00, Co:6.40-41.S0 and Hg:0.04-0.S3mg kg:' dry weight. The data showed considerable variation in the values from one sampling station to the other. IIighest values of metals were obtained at sampling station 3(Iddo).